Impact behaviour of hybrid basalt/flax twill laminates. (15th November 2018) - Papa, I.; Ricciardi, M.R.; Antonucci, V.; Pagliarulo, V.; Lopresto, V.
Abstract: The purpose of hybridization is to obtain a new material preserving advantages from all of its constituents. Hybridization offers intermediate properties respect to the original materials, by creating a balance effect within the fibres incorporated in the composite materials and leading to a composite with more tailored behaviour The increasing need to mitigate the environmental impact of synthetic fibres and polymers is promoting the use and application of natural materials orienting the research toward the development of biodegradable systems. In this framework, hybrid reinforced laminates with flax and basalt twill layers alternatively stacked, were manufactured by resin infusion fabrication technology and impacted at low velocity to investigate their dynamic behaviour, in an attempt to couple the impact resistance of basalt fibres with the environmentally friendly nature of flax fibres. For comparison purposes, the same experimental characterization has been performed on laminates reinforced with only basalt or flax fibres. The experimental results confirmed the positive role played by fibre hybridization in terms of damage. The Electronic Speckle Pattern Interferometry technique was adopted to analyze the internal damage and to provide information on the shape and the extent of the delamination, that was found concentrated under the impactor-material contact point for the basalt and flax/basalt laminates.